PENATALAKSANAAN FISIOTERAPI PADA ANAK CEREBRAL PALSY DENGAN KONDISI CONGENITAL TALIPES EQUINO VARUS MENGGUNAKAN METODE NEURO DEVELOPMENT TREATMENT - Lazimah .; Nur Susanti (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2013)
Congenital talipes equino varus or usually called by club foot is deformity that commonly occured in children. The factor which affect occuring CTEV at cerebral palsy is disturbance for intrauterine mechanical  which  caused  aberration  of fetus  development  during  pregnancy.  Problems  regarding condition  of  Cerebral  palsy with  CTEV  is  limited  of  base  of  support  so  the  kid  will  obtain disturbance in functional ability specially for self balancing in standing and walking. Because this matter also supported by postural control required skin touch of foot. Intervention including all of phisiotherapy measurement that is an examination for spasticity by Asworth Scale, an examination for identifying  in serious condition of CTEV by the pirani scoring system and an examination for functional  ability by  Gross  Motor  Functional  Measurement  (GMFM). In this  case  to  contend  the problems  above  may  used  modality  sort  of  Neuro  Development  Treatment.  From  the  result obtained. It can concluded that use of NDT can help reduce the problems that arise in this case.Key words : Congenital Talipes Equino Varus, Cerebral Palsy and Neuro Development Treatment.